Analisis Sosiologi Sastra pada Puisi Karya Emha Ainun Nadjib yang Berjudul “WIRID ORANG TERTINDAS” Sebagai Pembelajaran Sastra di Masyarakat - Yuwafa Faurelio Yahya; Akhmad Fatoni (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the religious values ​​in the poem Wirid Orang Tertindas by Emha Ainun Nadjib. The method used in this study is descriptive qualitative through a religious approach, the data collection technique in this study is using the reading and note-taking technique. In accordance with the results of the study, religious values ​​are found in the poem Wirid Orang Tertindas by Emha Ainun Nadjib, including the values ​​of faith and piety. Based on the results of the analysis, literary works that contain religious values ​​can be used as learning in society.